THE POTENTIAL USE OF Phaleria macrocarpa LEAVES EXTRACT AS AN ALTERNATIVE DRUG FOR BREAST CANCER AMONG WOMEN LIVING IN POVERTY - Amir, Hermansyah; Murcitro, Bambang Gonggo; Ahmad, Ahmad Shamsudin; Kassim, Murni Nur Islamiah (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2017)
Cancer is recognized as global threat to human development and it was estimated that in 2030 there will be 22.2 million new cases of cancer and 12.7 million cancer-related deaths worldwide. Herbal medicine plant till this day all over in the word is still the main source and one of the most important fields of traditional medicine agents to fight breast cancer. The usage of plants is still important because has its own beaviour advantages such as low toxicity, easy to get, cheap and has less side effect if it is used in a right. One of this plant it has been used as a traditional medicine is a Phaleria macrocarpa (Scheff) Boerl) also known as Mahkota Dewa from Papua island. It has been used traditionally for treatment of cancers in Indonesia and also to cure many diseases. The therapeutic effect of Phaleria macrocarpa (Scheff) Boerl, is related to the its bioactive compounds contents. There are many reported compounds from Phaleria macrocarpa (Scheff) Boerl, which are found, reported and published such as Icariside, phalerin, mangiferin, gallic acid, 29-Norcucurbitacin, gentiobioside and glucoside. All compounds reported above have already published as anticancer agents,where anticancer activity were detected and showed against Hela cells, leukemia cells, cervical cancer, breast cancer, and L1210 cells. Research on Phaleria macrocarpa (Scheff.) Boerl fruit and leaves merit have been done and published, however, there are very limited research on linked correlation between the concentration of compounds and its the cytotoxicity Â level. Because of that, research about correlation level of Phaleria macrocarpa (Scheff) Boerl leaves extract still need to investigate to find the relationship between them in the goal to investigate alternative low cost herbal medicine agents to fight breast cancer especially useful for low income people, thus, information about Phaleria macrocarpa (Scheff.) Boerl.Leaves became more complete. Cytotoxicity properties of samples against breast cancer cell lines was performed by using the MTT assay against MCF-7 cell line. The correlation between concentration of crude and cytotoxic activity was interpreted by statistical analyses. The study showed that Phaleria macrocarpa (Scheff) Boerl.) leaves extracts showed cytoxicity activity against breast cancer MCF7 cell lines. Correlation between concentration of extract and cytotoxicity property (absorbance value) were founded in weak relationship (R = -0.37181). It could be effect of many different compounds in the Phaleria macrocarpa (Scheff) Boerl.) leaves methanol extracts may cause the pharmacological interactions, so lower or higher concentration will be antagonistic effect on absorbance or cell viability.Further study on its mechanism pathway on revealing against breast cancer could be explored. Furthermore, the natural product derived from Phaleria macrocarpa (Scheff) Boerl.) leaves extracts have potential use in cheap alternative agents against breast cancer